2005
DOI: 10.1002/ca.20234
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical contribution of the fibula to torsion stiffness in the lower extremity

Abstract: The role of the fibula in rotational stability of the lower extremity, taking into account the intact knee joint and tibia, to the best of our knowledge, has not been investigated. A cadaver study was designed to determine the torque transfer down the lower extremity, with and without the fibula. Six fresh, frozen human cadaver legs were used. The knee joint was left intact and the foot disarticulated. An external rotation up to 5 degrees , coupled with axial compression, was applied to the femur passing throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…7,13,14 Although their material properties are not completely representative of cadaveric tibia, they similarly offer much less inter-specimen variability. 2,7,10,13,18,25,28 The combined attributes of uniform geometry, accurate biomechanical properties, and reduced inter-specimen variability limits the number of factors that could contribute to inconsistencies in the experimental study including different anatomic geometries and bone quality found in cadaveric human tibiae. Because of the uniformity in specimens, we were able to use plates and screws of the same size for each tibia, insuring bicortical purchase with each installation, similar levels of fracture reduction, and similar positioning of the plates, while following standard operative technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,13,14 Although their material properties are not completely representative of cadaveric tibia, they similarly offer much less inter-specimen variability. 2,7,10,13,18,25,28 The combined attributes of uniform geometry, accurate biomechanical properties, and reduced inter-specimen variability limits the number of factors that could contribute to inconsistencies in the experimental study including different anatomic geometries and bone quality found in cadaveric human tibiae. Because of the uniformity in specimens, we were able to use plates and screws of the same size for each tibia, insuring bicortical purchase with each installation, similar levels of fracture reduction, and similar positioning of the plates, while following standard operative technique.…”
Section: Discussionmentioning
confidence: 99%
“…Although the tibia is primarily responsible for resisting compressive loads, some uncertainty exists as to the fibula's contribution to resisting torsional loads. 18,25 Finally, our loading design does not account for all of the complexities seen in a tibia loaded by the femoral condyles and talus, nor by complex muscular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…While both bones share loading, and thus work together to resist the loads encountered in habitual activity, our results support this argument, further suggesting that the tibia and fibula also compensate for one another. As reviewed in the Introduction, researchers (e.g., Thambyah and Pereira, ; Cristofolini et al, ) have argued that the fibula mitigates some of the loads that the tibia would otherwise have experienced. Our results indicate that this is the case only for the anatomical position of the fibula in cross‐section; tibial minimum bending rigidity increases as the fibula is located more posteriorly.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the fibula may provide substantial load reduction for the tibia. In particular, torsional forces from the femur on the tibia may be mitigated by the fibula (Thambyah and Pereira, ), partly as a result of anteroposterior movement of the fibular head during internal and external rotation of the lower limb (Scott et al, ). Although the femur and tibia have one to two magnitudes greater stiffness than the fibula, stiffness and strain distribution on the same plane among all three bones are similar when subjected to bending and torsion (Cristofolini, Schileo, Juszczyk, Taddei, Martelli, & Viceconti, ).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have also demonstrated load transfer through the interosseous membrane, which connects the tibia and fibula (Skraba and Greenwald, 1984, Thomas et al, 1995, Vukicevic et al, 1980, Wang et al, 1996. In addition to its axial load-sharing role, the fibula has also been shown to contribute to the rotational stiffness of the lower leg (Thambyah and Pereira, 2006).…”
Section: Introductionmentioning
confidence: 99%